Accommodating Diverse Learning Styles in Undergraduate Chemistry: A Mixed-Methods Study on Differentiated Interactive Learning Materials - Munawwarah, Munawwarah; Side, Sumiati; Ilmi, Nurul (Jurnal Pendidikan MIPA, 2025)
This study investigates chemistry students’ perceptions of Interactive Learning Materials (ILMs) developed using a differentiated instruction approach. The research employed a mixed-methods design involving 62 undergraduate students in the Chemistry Education Program, Universitas Negeri Makasar, Indonesia, who completed a perception questionnaire and a validated online learning-style assessment. Descriptive analysis revealed that students’ overall perceptions of the ILMs were highly positive across six dimensions: preliminary experience, relevance, conceptual comprehension, differentiation, motivation, and effectiveness. In addition, a Kruskal–Wallis inferential test was conducted on a subset of 46 valid respondents to examine whether perception scores differed significantly across learning-style groups. The results indicated no statistically significant differences among the seven learning-style categories (H (6, 46) = 4.72, p = .58), suggesting that the ILMs were perceived positively and consistently across all groups. Qualitative responses further supported these findings, highlighting that kinesthetic learners valued interactive features but desired richer hands-on engagement. Overall, the study confirms that ILMs with differentiated pathways can effectively support diverse learners in mastering abstract chemistry concepts, while emphasizing the need for future development to integrate more kinesthetic and exploratory elements.   Keywords: interactive learning materials, differentiated instruction, learning styles, chemistry education, student perceptions.